A performance evaluation model for transportation projects based on principal component analysis. (19th May 2018) - Zhao, Q.; Zhou, Y.; Guo, W.
Abstract: This study investigates the performance evaluation problem, which plays an important role in transport transit project supported by finance. In this paper, firstly it puts forward the evaluation indicators of transport transit project, and indicators of cause and outcome are considered; secondly, PCA (Principal Component Analysis) method is developed to take empirical researches on performance evaluation of transport transit project supported by finance. Thus, the overall development of transport transit project can be got quantitatively. At last, some important conclusions are obtained: the degree of project development is quite different; project 1 takes the leading place, while project 4 is lagging behind; project 1 fully complies with the rules and regulations, etc. Study findings and feasible suggestions are provided for academics and practitioners.